A formal Anthropocene is compatible with but distinct from its diachronous anthropogenic counterparts: a response to W.F. Ruddiman's 'three flaws in defining a formal Anthropocene'. (June 2019) - Zalasiewicz, Jan; Waters, Colin N; Head, Martin J; Poirier, Clément; Summerhayes, Colin P; Leinfelder, Reinhold; Grinevald, Jacques; Steffen, Will; Syvitski, Jaia; Haff, Peter; McNeill, John R; Wagreich, Michael; et al.
We analyse the 'three flaws' to potentially defining a formal Anthropocene geological time unit as advanced by Ruddiman (2018). (1) We recognize a long record of pre-industrial human impacts, but note that these increased in relative magnitude slowly and were strongly time-transgressive by comparison with the extraordinarily rapid, novel and near-globally synchronous changes of post-industrial time. (2) The rules of stratigraphic nomenclature do not 'reject' pre-industrial anthropogenic signals – these have long been a key characteristic and distinguishing feature of the Holocene. (3) In contrast to the contention that classical chronostratigraphy is now widely ignored by scientists, it remains vital and widely used in unambiguously defining geological time units and is an indispensable part of the Earth sciences. A mounting body of evidence indicates that the Anthropocene, considered as a precisely defined geological time unit that begins in the mid-20th century, is sharply distinct from the Holocene.